Design And Development Of A Web-Based Attendance System For Daily Workers At The Civil Service Police Unit Office Of Bengkulu Province - Mardiansyah Mardiansyah; Khairil Khairil; Ricky Zulfiandry (Jurnal Media Computer Science, 2026)
In the current digital era, the need for efficient and accurate systems is increasingly urgent, especially in supporting administrative data management in government agencies. One important aspect of administrative management is workforce attendance, which serves as a basis for performance evaluation. However, in the Office of the Civil Service Police Unit (Satpol PP) of Bengkulu Province, the attendance system for daily workers still faces significant challenges. Therefore, this study aims to design a web-based attendance system for daily workers in the Office of Satpol Pamong Praja of Bengkulu Province. The research method used is the waterfall system design method. The attendance system has been successfully developed and implemented with a simple, intuitive interface that meets user needs and operates well within the environment of the Office of the Civil Service Police Unit of Bengkulu Province. This system is capable of managing employee data, recording attendance, and generating structured and automated attendance reports.